A new varying arm length (VAL) based technique for increasing payload quadrotor under pid control - Najm, Yasameen Kamil (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2016)
This research focuses on the enhancement of quadrotor performance in terms of stability and payload capability by designing a simple reconfigurable controlling system. Varying the arm's length is utilized to varying the torque around the center of the mass to control the attitude angles, x-, and y-position. The new quadrotor technique focusing on fixing all motors speed and varying the arms length of the quadrotor. Also, this leads to reduce the complexity of the control system by converting it from second order system to a first order. The new design is called VAL-quadrotor. MATLAB software is used to implement the simulation program (code) of VAL-quadrotor. The validity of VAL-quadrotor is tested by comparing the result with the conventional quadrotor in ideal environments. In addition, VAL-quadrotor can exploit maximum motors speed to carry extra load and perform maneuvers using the arm's length which is an important factor for using quadrotor as unmanned couriers for delivery and crop dusting. Furthermore, this design enables the VAL-quadrotor to change its size according to the required mission by reducing the length of the arms of the VAL-quadrotor to minimum to make the VAL-quadrotor smaller in size and be controlled as a conventional quadrotor by varying motors speed. This would make the VAL-quadrotor be able to fly through small windows or doors, and monitoring environtmental disasters unreachable by humans.